Consórcios públicos intermunicipais e emendas orçamentárias individuais: indução recíproca por meio da ação coletiva - Cotta, Márcia Aparecida (2019)
Considering a general approach, the dissertation, based on the neoinstitutional theory, reveals the cooperative federative relations established in two planes: (i) horizontal, regarding the implementation of public policies carried out through Intermunicipal Public Consortia (IPC) and (ii) vertical, in relation to voluntary fund transfers from the Union Budget (UB) to a consortium of Municipalities. Development and decrease in territorial inequality were identified in the essence of the purposes of Public Consortia and Voluntary Discretionary Transfers (VDT), focused in the context of cooperative federalism. The theoretical debate was shaped according to the collective action, centered on public policy and advocacy. Of applied nature, qualitative approach and descriptive characteristic, the research was based on bibliographic and documentary procedures, which data was subjected to content analysis with the Atlas IT 8.1 software. The research turned itself to investigate how voluntary discretionary transfers by individual parliamentary amendments to the Budget of the Union appear as an incentive to the cooperation between Municipalities formalized by public consortium. By relating the analyzed content to the data of the UB, that point out that the most expressive part of the VDT by individual parliamentary amendment (IPA) is not directed to IPC, the following conclusions were, in summary, reached: (i) the rules of the game, which structure the objects of research, contain cooperative elements, however some contextual components obstruct generalization of this perspective; (ii) political behavior is expressed by inclusive and integrative strategies, but also by movements of an autarchic, utilitarian and individualistic nature; (iii) the role of leadership, besides technical, political and of legitimacy, is relevant in fostering cooperation and popular participation in decision-making processes; (iv) collective action, which allocates the implementation of public policy as a main concern, also refers to the representation of interests of the IPC in obtaining funds from budgetary transfers. The conclusions, which converged towards the same idea, revealed that, although the VDT processed by IPA influences the intermunicipal cooperation formalized by consortia, the influence comes from the mere expectation regarding the reception of the resources, molded from the formal and informal rules of the game that structure the situations of action.